Association of the sarcopenia index with cognitive impairment in a middle-aged to older patients with acute ischemic stroke or transient ischemic attack: A multicenter cohort study - Siqi Li; Hongyi Yan; Yuesong Pan; Yumei Zhang (Elsevier, 2024)
Objectives: The sarcopenia (SI) index, defined as the serum creatinine to cystatin C ratio, is considered a predictor of poor muscle health and malnutrition, which is related to major adverse cardiovascular events. However, the effect of the SI index on cognitive function in stroke patients remains unknown. In this study, we aimed to examine the association between the SI and longitudinal cognitive impairment in patients with acute ischemic stroke or transient ischemic attack. Research design and methods: Participants who met the inclusion criteria in this national, multicenter, prospective cohort study were enrolled from the Impairment of Cognition and Sleep (ICONS) study of the China National Stroke Registry-3 (CNSR-3). They were categorized into four groups according to the quartile of the SI index. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) scale. Multivariable-adjusted logistic regression models were performed to evaluate the association between the SI index and post-stroke cognitive impairment (PSCI) at the 3-month follow-up. Moreover, discrimination tests were used to evaluate the incremental predictive value of the SI index beyond the potential risk factors. Furthermore, we performed subgroup analyses to test interactions. Results: Among the enrolled participants, the lower the SI index was, the worse the cognitive performance. At the 3-month follow-up, participants in the lowest SI quartile group exhibited a 42% increase in the risk of cognitive impairment relative to the highest quartile group [OR 0.58 (95% CI 0.37-0.90)]. Moreover, after applying the discrimination test, adding the SI index into the potential risk factors resulted in a slight improvement in predicting the risk of cognitive impairment [NRI 14% (P = 0.01)]. Conclusion: This study demonstrated that a lower sarcopenia index was positively associated with a higher prevalence of PSCI. Monitoring the SI index in stroke patients and early identification and treatment of individuals with low SI level may be helpful to reduce the risk of cognitive impairment.